2019
DOI: 10.1007/s40094-019-00363-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study to find suitable dopants of CdS buffer layer for CZTS solar cell

Abstract: The performance of CZTS solar cell, a promising candidate in the field of energy production from sunlight, can be improved by optimizing the parameters of most widely used CdS buffer layer. In this work, numerical study have been done on the typical CZTS solar cell structures containing Mo thin film as back contact on glass substrate using SCAPS-1D solar cell simulation software. Then, the CZTS has been used as the absorber layer followed by CdS buffer later. Following, ZnO and transparent conducting oxide n-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The performance of proposed cell structure is found comparable with the standard solar cell structures (ZnO:Al/ZnO/CdS/CZTS/Mo) with CZTS as a harvesting layer (Jhuma et al 2019, Cantas et al 2018. These CZTS cells are conventionally fabricated using CdS, CdTe or CdZnS as the buffer layer which have toxic component, and it is expected to avoid the use of cadmium (Jhuma et al 2020). In the presented work ZnTe is investigated as the buffer layer, as ZnTe is cost effective, earth abundant and eco-friendly material.…”
Section: Introductionmentioning
confidence: 76%
“…The performance of proposed cell structure is found comparable with the standard solar cell structures (ZnO:Al/ZnO/CdS/CZTS/Mo) with CZTS as a harvesting layer (Jhuma et al 2019, Cantas et al 2018. These CZTS cells are conventionally fabricated using CdS, CdTe or CdZnS as the buffer layer which have toxic component, and it is expected to avoid the use of cadmium (Jhuma et al 2020). In the presented work ZnTe is investigated as the buffer layer, as ZnTe is cost effective, earth abundant and eco-friendly material.…”
Section: Introductionmentioning
confidence: 76%
“…CZTS layer works as a p-type absorber layer. Most of the incident photons are absorbed by this layer to generate electron hole pair [27]. Next to the absorber layer is buffer layer where n-CdS is used in the conventional thin film solar cells.…”
Section: A Device Structurementioning
confidence: 99%
“…Molybdenum (Mo) was inserted as back-contact metal on glass substrate. The physical parameters of the materials CZTS, Zn(S, O), and ZnO:I used in the simulation are listed in Table 5, which are considered to be constant during the simulation under the illumination of the AM 1.5 standard spectrum and temperature fixed at 300 K. [49,50] The purpose of using Zn(S, O) as a buffer layer instead of CdS is to investigate the performances of an abundant and nontoxic solar cell. Mahbub et al found that the solar cell with ZnS buffer layer has the highest efficiency (efficiency ¼ 26.82%, FF ¼ 69.44%, J sc ¼ 53.312 mA cm À2 , and V oc ¼ 0.724 V) among all other considered buffer layers such as CdS, In 2 S 3 , and ZnSe.…”
Section: Simulation Partmentioning
confidence: 99%